Iron Deficiency Without Anemia in Athletes: Pathophysiology, Diagnosis, and Modern Management Strategies - Superson, Katarzyna; Mszyca, Igor; Browarska, Emilia; Miemczyk, Katarzyna; Wołek, Filip Tadeusz; Michalski, Łukasz; Gajewska, Nicole; Mularczyk, Karolina Natalia; Kucharski, Kacper; Aksamit, Anna (Quality in Sport, 2026)
Background: Iron deficiency without anemia (IDNA) is a metabolic condition in which the depletion of systemic stores impairs physical performance despite normal hemoglobin concentrations. It affects up to 35% of female athletes overall, with the prevalence of latent hypoferritinemia (<50 ug/L) reaching as high as 53.9% among female collegiate athletes. Pathophysiology & Diagnosis: At the subcellular level, iron deficiency impairs mitochondrial oxidative phosphorylation, inducing an inefficient metabolic shift toward anaerobic glycolysis and causing a 3–19% reduction in endurance capacity. The diagnosis is primarily established based on serum ferritin and transferrin saturation (TSAT) levels. Management: Therapeutic approaches include dietary counseling and oral iron supplementation (16–100 mg of elemental iron), with alternate-day dosing regimens demonstrating high efficacy in minimizing the hepcidin blockade and improving gastrointestinal tolerance. Intravenous (IV) iron supplementation remains a second-line therapeutic option, reserved for athletes with severe malabsorption, non-responders to oral protocols, or under critical time constraints before competitions. Conclusions: Early screening and tailored supplementation strategies are essential to mitigate performance declines and maintain biochemical homeostasis in athletic populations.